The Relationship between Democratic Parenting Styles and Independence in Mobility Orientation of Visually Impaired Students in Special School in The Solo Raya Region - Prakosha, Donni; Hasanah, Mutmainnatul; Supriyadi, Supriyadi (Journal of ICSAR, 2024)
This study aims to determine the relationship between democratic parenting styles and independence in the mobility orientation of visually impaired students in special school in the Solo Raya region. The quantitative correlational method was employed, with the research subjects consisting of 30 parents of visually impaired students aged 7-15 years in special school in the Solo Raya region. The sampling technique used was probability sampling through cluster random sampling. Data collection was conducted using a non-test instrument (scale). The analysis technique employed was the Pearson Product Moment correlation with the assistance of SPSS 26. The results of this study showed a significance level of 0.507, indicating a linear relationship between the two variables. The correlation coefficient value in the hypothesis test results between the two variables was 0.757, indicating a strong level of association. The conclusion, it can be concluded that there is a relationship between parental democratic parenting and the independence of mobility orientation of blind students in SLB in the Solo Raya region with a correlation.